BoardMe App : a mobile application for finding a boarding house in Sampaloc, Manila - Abella, Meldrick F.; Fajardo, Gideon Gerald R.;Pascual, Lyka G.;Pecdasen, Lander M. (Manila : National University, 2016)
Board Me App is a mobile application that helps the tenants to find the nearest boarding houses and give them the geographic information easily.
Chapter 1. Introduction -- Chapter 2. Review of related literature/studies -- Chapter 3. Technical background -- Chapter 4. Methodology, results and discussion -- Chapter 5. Summary of findings and recommendation.
Includes bibliographical references.